Carbon Emissions Assessment Fly ash and Steel Slag As a Substitute for Cement in Concrete Mixing Using the Method Artificial Neural Networks - Salma Fauziyyah (Structure, 2023)
Concrete is a construction material made from a mixture of Portland cement, air, coarse aggregate, fine aggregate, and sometimes also uses admixture materials with a certain ratio. Cement, which is the binding agent in the concrete mixture, contributes to 8% of the world's carbon dioxide (CO2) emissions. Fly ash and steel slag are one of the wastes that are currently being researched and developed as cement ingredients in concrete mixtures. This is because the chemical composition of fly ash and slag associated with cement is very suitable when added to concrete mixtures.This study aims to find out of the optimal of fly ash and slag content in the concrete mixture in terms of strength by using the Artificial Neural Network (ANN) method and in accordance with SNI 7656: 2012. Furthermore, this study also aims to measure the ratio of CO2 emissions that are produced from normal concrete, concrete with fly ash, and concrete with steel slag, using references from Idemat2014 and Ecoinvent V3.The results showed that the optimum content of fly ash class F, fly ash class C, and steel slag in the concrete mixture were 30%, 20%, and 55%, respectively. The results also concluded that steel concrete slag as the lowest emitter of CO2 compared to normal concrete, class F fly ash concrete, and class C fly ash concrete. Keywords: concrete, fly ash, steel slag, ANN, comppresive strength, CO2 emission